Elliptically polarizing plate and image display device

By using an elliptical polarizer with a thickness of more than 15 μm in the vehicle-mounted image display device, combined with phase difference layer and liquid crystal orientation technology, the problem of reflective light coloring around the special-shaped processing part in a high-temperature environment is solved, and stable image display characteristics are achieved.

CN119861443APending Publication Date: 2025-04-22NITTO DENKO CORP
View PDF 24 Cites 0 Cited by

Patent Information

Application Number
CN202411451462.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-10-19
Filing Date
2024-10-17
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

In a high temperature environment, the circular polarizer used in the vehicle-mounted image display device is prone to coloring problems of reflected light around the special-shaped processing part.

Method used

An elliptical polarizer having a transparent protective film is used, and the polarizer thickness is 15 μm or more, and a phase difference layer is bonded to one side of the polarizer. The phase difference layer includes at least one layer of an oriented liquid crystal layer with liquid crystal molecules oriented along the plane. The absorption axis direction of the polarizer forms an angle of 10 to 80° with the slow axis direction of the phase difference layer, which satisfies the frontal delay relationship of the phase difference layer at different wavelengths.

Benefits of technology

Even in a high temperature environment, the frontal retardation of the phase difference layer is small, which can effectively suppress the visibility changes around the special-shaped processing section and reduce the coloring of reflected light.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119861443A_ABST
    Figure CN119861443A_ABST
Patent Text Reader

Abstract

This elliptical polarizing plate (101) is provided with: a polarizing plate (1) provided with transparent protective films (11, 12) on both surfaces of a polarizer (10) having a thickness of 15 [mu] m or more; and a phase difference layer (3) bonded to the transparent protective film (1) of the polarizing plate. The elliptical polarizer has a special shape. The angle formed by the absorption axis direction of the polarizer (1) and the slow axis direction of the phase difference layer (3) is 10-80 degrees. The front retardation Re (450) at a wavelength of 450 nm, the front retardation Re (550) at a wavelength of 550 nm, and the front retardation Re (650) at a wavelength of 650 nm of the phase difference layer (3) satisfy Re (450) lt; re (550) lt; and Re (650), and includes at least one oriented liquid crystal layer in which liquid crystal molecules are oriented along the surface.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an elliptically polarizing plate including a phase difference layer on one main surface of a polarizing plate, and an image display device including an elliptically polarizing plate on the surface of an image display unit. Background Art

[0002] Mobile phones, smart phones, car navigation devices, monitors for personal computers, televisions, etc. are display devices with image display elements, and as image display elements, they are equipped with liquid crystal display devices and organic EL display devices. Due to its display principle, the liquid crystal display device is equipped with a polarizer on the visible side surface of the image display unit. In addition, in the organic EL display device, in order to suppress the external light from being reflected by the metal electrode (cathode) and being visible like a mirror, an elliptical polarizer (for example, a circular polarizer formed by laminating a polarizer and a 1 / 4 wavelength plate) is arranged on the visible side surface of the image display unit.

[0003] In recent years, the adoption of thinner and curved organic EL display devices has progressed, and organic EL display devices have also been adopted for instrumentation instruments installed in dashboards and consoles of automobiles. Optical films such as polarizing plates used in these display devices are sometimes processed into shapes that are not rectangular in top view (irregular shapes) (for example, see Patent Document 1).

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2022-47611 Summary of the invention

[0007] Problems to be solved by the invention

[0008] In-vehicle image display devices are required to have little change in display characteristics even in harsh environments such as high temperature and high humidity. However, image display devices having a circular polarizer processed by profile processing on the surface of an organic EL unit have a problem that the coloring of reflected light around the profile processing parts such as notches and cuts becomes easily visible if they are exposed to a high temperature environment for a long time.

[0009] In view of the above, an object of the present invention is to provide an elliptically polarizing plate in which a change in visibility at the periphery of a profiled processed portion is suppressed.

[0010] Means for solving problems

[0011] The present invention relates to a single-piece elliptical polarizing plate having an irregular shape that is not rectangular in a plan view. The elliptical polarizing plate comprises a polarizing plate having transparent protective films on both sides of a polarizer having a thickness of 15 μm or more, and a phase difference layer attached to the transparent protective film on one side of the polarizing plate. The angle formed by the absorption axis direction of the polarizer and the slow axis direction of the phase difference layer is 10 to 80°. The front retardation Re(450) of the phase difference layer at a wavelength of 450 nm, the front retardation Re(550) at a wavelength of 550 nm, and the front retardation Re(650) at a wavelength of 650 nm satisfy Re(450) <Re(550)<Re(650)。

[0012] The phase difference layer includes at least one oriented liquid crystal layer in which liquid crystal molecules are oriented along the surface. The phase difference layer may also include two or more oriented liquid crystal layers, wherein at least one layer is a liquid crystal layer oriented along the surface. The phase difference layer may also include two or more oriented liquid crystal layers oriented along the surface. The phase difference layer may also include an oriented liquid crystal layer in which liquid crystal molecules are oriented along the surface and an oriented liquid crystal layer in which liquid crystal molecules are oriented vertically.

[0013] The elliptically polarizing plate of the present invention can be suitably used for forming a vehicle-mounted image display device. In one embodiment, the elliptically polarizing plate is disposed on the visible side surface of the image display unit for use. The image display unit may also be an organic EL unit.

[0014] Effects of the Invention

[0015] The elliptically polarizing plate of the present invention has a small change in the front retardation of the phase difference layer even when it is exposed to a high temperature environment for a long time, and can suppress the change in visibility around the irregularly processed portion. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1A , Figure 1B , Figure 2C , Figure 2D , Figure 2E , Figure 2F , Figure 2G , Figure 2H , Fig.2I , Figure 2J , Figure 2K , Figure 3L and Figure 3M Each of them is a schematic plan view for explaining the planar shape of an irregular elliptically polarizing plate.

[0017] Figures 4 to 6 Each of them is a cross-sectional view of an elliptically polarizing plate according to one embodiment.

[0018] Figure 7 It is a cross-sectional view showing an example of a stacked structure of an image display device.

[0019] Figure 8It is a diagram for explaining the delay change of the irregularly processed portion.

[0020] Fig. 9 The diagram shows the planar shape of the irregular circular polarizing plate produced in Examples and the measurement position of the front retardation.

[0021] Fig. 10A and Fig. 10B This is a graph in which the reflection hues of the circularly polarizing plates of Comparative Example 1 and Example 2 are plotted.

[0022] Explanation of symbols

[0023] 1 Polarizer

[0024] 10 Polarizer

[0025] 11, 12 Transparent protective film

[0026] 3 phase difference layer

[0027] 31 phase difference layer (plane-aligned liquid crystal layer)

[0028] 32 phase difference layer (plane-aligned liquid crystal layer)

[0029] 33 phase difference layer (plane-aligned liquid crystal layer)

[0030] 36 phase difference layer (vertical alignment liquid crystal layer)

[0031] 101, 102, 103, 105 ellipsoidal polarizers

[0032] 50 Image display unit

[0033] 201 Image display device DETAILED DESCRIPTION

[0034] The present invention relates to a single-piece elliptically polarizing plate having a shape that is not rectangular (irregular shape) in a plan view. Figure 1A , Figure 1B , Figure 2C , Figure 2D , Figure 2E , Figure 2F , Figure 2G , Figure 2H , Fig.2I , Figure 2J , Figure 2K , Figure 3L and Figure 3M This is a plan view for explaining the planar shape of an irregular elliptically polarizing plate. Figures 4 to 6 It is a cross-sectional view of an elliptically polarizing plate according to an embodiment of the present invention.

[0035] The elliptically polarizing plate of the present invention comprises a polarizing plate 1 having transparent protective films 11 and 12 bonded to both surfaces thereof and a retardation layer 3 on the transparent protective film 11. The angle formed by the absorption axis direction of the polarizer 10 and the slow axis direction of the retardation layer 3 is 10 to 80 degrees.

[0036] [Shape of elliptically polarizing plate]

[0037] The term "irregular shape" in this specification means that the top view shape has a shape other than a rectangle. An irregular elliptical polarizing plate typically has an irregularly processed portion. An irregular elliptical polarizing plate includes an elliptical polarizing plate whose outer edge shape is not rectangular because the outer edge of the elliptical polarizing plate has an irregularly processed portion, an elliptical polarizing plate having an irregularly processed portion in a portion spaced inward from the outer edge of a rectangular elliptical polarizing plate, and an elliptical polarizing plate having an irregularly processed portion in both the outer edge and the portion spaced from the outer edge.

[0038] As the irregular shape (irregular shape processed part), for example, Figure 1A , B and Figure 2C As shown in Figures 1 to 4, a special shape having a cut-processed portion that becomes a concave portion when viewed from above, or a special shape having a through hole. Representative examples of the concave portion include a shape similar to a boat shape, a rectangular shape, an R shape similar to a bathtub shape, a V-shaped notch, and a U-shaped notch. Other examples of the special shape (special shape processed portion) include Figure 3L As shown in , M, a shape corresponding to an instrument panel of an automobile can be listed. This shape includes a portion where the outer edge is formed in an arc shape along the rotation direction of the instrument needle and the outer edge is formed in a V shape (including an R shape) convex inward in the surface direction.

[0039] The shape of the irregular shape (irregular shape processing part) is not limited to the examples shown in Figures 1 to 3. For example, the shape of the through hole can also be an ellipse, a triangle, a quadrilateral, a pentagon, a hexagon, an octagon, etc. In addition, the through hole is set at any suitable position according to the purpose. The position of the through hole is not particularly limited. It is also possible to set a plurality of through holes on one elliptical polarizer.

[0040] The shape of the elliptical polarizer may also be a combination of a plurality of special-shaped processing shapes. Figure 1A or Figure 1B A through hole may be formed at any position of the elliptical polarizing plate having an outer edge shape. Figure 3L or Figure 3M A V-shaped or U-shaped notch is formed at an arbitrary position of the elliptically polarizing plate having the outer edge shape.

[0041] When the irregularly shaped portion includes an R shape, its curvature radius is, for example, 0.2 mm or more, or 0.5 mm or more, 1 mm or more, or 2 mm or more. The curvature radius of the irregularly shaped portion is, for example, 10 mm or less, or 7 mm or less, or 5 mm or less.

[0042] The irregularly shaped processed portion can be formed by any appropriate method. Examples of the processing method include cutting with an end mill, punching with a Thomson cutter, a Pinnacle cutter, etc., and cutting with laser irradiation.

[0043] Such a shaped elliptically polarizing plate can be suitably used in image display devices for vehicle-mounted applications such as automobile instrument panels, and image display devices for mobile applications such as smartphones, tablet PCs, and smart watches. As described in detail below, the elliptically polarizing plate of the present invention is particularly suitably used in vehicle-mounted image display devices.

[0044] [Laminated structure of elliptically polarizing plates]

[0045] Figure 4 It is a cross-sectional view of an elliptically polarizing plate according to one embodiment of the present invention. An elliptically polarizing plate 101 includes a retardation layer 3 on one surface of a polarizing plate 1 including transparent protective films 11 and 12 on both surfaces of a polarizer 10 .

[0046] <Polarizing Plate>

[0047] Examples of the polarizer 10 of the polarizing plate 1 include a polarizer obtained by adsorbing dichroic substances such as iodine and dichroic dyes onto a hydrophilic polymer film such as a polyvinyl alcohol film or a partially saponified film of an ethylene-vinyl acetate copolymer and then uniaxially stretching the film; and polyene-based oriented films such as a dehydrated product of polyvinyl alcohol or a dehydrochlorinated product of polyvinyl chloride.

[0048] From the perspective of high polarization degree and durability at high temperature, a polyvinyl alcohol (PVA) film containing iodine is preferably used as the polarizer 10. As the material of the PVA film used for the polarizer, polyvinyl alcohol or its derivatives are used. As derivatives of polyvinyl alcohol, polyvinyl formal, polyvinyl acetal, etc. can be listed, and substances modified by olefins such as ethylene and propylene, unsaturated carboxylic acids such as acrylic acid, methacrylic acid, crotonic acid, and their alkyl esters, acrylamide, etc. can also be listed. Polyvinyl alcohol generally uses polyvinyl alcohol with a degree of polymerization of about 1000 to 10000 and a saponification degree of about 80 to 100 mol%.

[0049] A polarizer can be obtained by dyeing the PVA film with iodine and stretching it. In the manufacturing process of the polarizer, it can also be washed, swollen, cross-linked, etc. as needed. Stretching can be performed at any time before or after iodine dyeing, or it can be stretched while dyeing. Stretching can be either stretching in the air (dry stretching), or stretching in water or in an aqueous solution containing boric acid, potassium iodide, etc. (wet stretching), or they can be used in combination.

[0050] The thickness of the polarizer 10 is 15 μm or more. The greater the thickness of the polarizer, the higher the durability at high temperatures, and the more suitable it is for vehicle-mounted applications. From the perspective of thinning, the thickness of the polarizer 10 is preferably 100 μm or less, and may also be 60 μm or less, 50 μm or less, or 40 μm or less.

[0051] <Transparent protective film>

[0052] The polarizing plate 1 includes transparent protective films 11 and 12 on both main surfaces of a polarizer 10. By bonding transparent protective films to both surfaces of the polarizer 10, changes in optical characteristics due to dimensional changes of the polarizer at high temperatures tend to be suppressed.

[0053] As a material constituting the transparent films 11 and 12 as polarizer protective films, a thermoplastic resin having excellent transparency, mechanical strength, and thermal stability is preferred. Specific examples of the thermoplastic resin include cellulose resins such as triacetyl cellulose, polyester resins, polyethersulfone resins, polysulfone resins, polycarbonate resins, polyamide resins, polyimide resins, polyolefin resins, (meth)acrylic resins, cyclic polyolefin resins (norbornene resins), polyarylate resins, polystyrene resins, polyvinyl alcohol resins, and mixtures thereof.

[0054] The transparent film 11 disposed on one surface of the polarizer 10 and the transparent film 12 disposed on the other surface may be films formed of the same resin material or may be films formed of different resin materials.

[0055] The thickness of the transparent films 11 and 12 is not particularly limited, but is preferably about 5 to 100 μm, more preferably 10 to 80 μm, from the viewpoints of strength, workability such as handleability, and thin film properties.

[0056] <Adhesive>

[0057] The polarizer 10 and the transparent protective films 11 and 12 are preferably bonded via a suitable adhesive layer (not shown). As the adhesive, various types of adhesives such as water-based adhesives, solvent-based adhesives, hot-melt adhesives, and active energy ray-curable adhesives are used. Among them, from the aspect of being able to reduce the thickness of the adhesive layer, a water-based adhesive or an active energy ray-curable adhesive is preferred. The material of the adhesive is not particularly limited as long as it is optically transparent, and examples include epoxy resins, silicone resins, acrylic resins, polyurethanes, polyamides, polyethers, polyvinyl alcohols, etc. The thickness of the adhesive is preferably 5 μm or less, more preferably 0.01 - 3 μm, and further preferably 0.05 - 2 μm.

[0058] <Retardation layer>

[0059] The elliptical polarizer 101 has a retardation layer 3 on the transparent protective film 11 of the polarizer 1. The retardation layer 3 may include one layer, or may be a laminate of multiple retardation layers as shown in Figure 5 , 6 .

[0060] The retardation layer 3 is arranged such that the angle formed by the absorption axis direction of the polarizer 10 and the slow axis direction of the retardation layer 3 is 10 - 80°. By arranging the absorption axis direction of the polarizer and the slow axis direction of the retardation layer at an angle that is neither parallel nor orthogonal, the linearly polarized light emitted from the polarizer 10 is converted into elliptically polarized light when passing through the retardation layer 3. Therefore, the laminate of the polarizer 1 and the retardation layer 3 functions as an elliptical polarizer.

[0061] The front retardation Re(450) at a wavelength of 450 nm, the front retardation Re(550) at a wavelength of 550 nm, and the front retardation Re(650) at a wavelength of 650 nm of the retardation layer 3 satisfy Re(450) < Re(550) < Re(650). Due to the characteristic of the retardation layer 3 having a greater retardation as the wavelength becomes longer (so-called "inverse wavelength dispersion"), the elliptical polarizer can emit uniform elliptically polarized light in a wide wavelength range of visible light.

[0062] In the retardation layer 3, Re(450) / Re(550) is less than 1, preferably 0.65 - 0.99, more preferably 0.70 - 0.95, further preferably 0.75 - 0.90, and may also be 0.80 - 0.85. In the retardation layer 3, Re(650) / Re(550) is greater than 1, preferably 1.01 - 1.35, more preferably 1.03 - 1.30, further preferably 1.05 - 1.25, and further preferably 1.10 - 1.20.

[0063] In one embodiment, the elliptical polarizer 101 is a circular polarizer in which the phase difference layer 3 is a 1 / 4 wavelength plate, and the angle between the absorption axis direction of the polarizer 10 and the slow axis direction of the phase difference layer 3 is approximately 45°. The circular polarizer having the phase difference layer 3 with reverse wavelength dispersion has a small difference between the front retardation of the phase difference layer and the 1 / 4 wavelength in the wide wavelength range of visible light, so the circularly polarized light is broadbanded. If a broadband circular polarizer is configured on the surface of the organic EL display device, the coloring of the reflected light is small, and excellent anti-reflection properties can be achieved.

[0064] In order to make the elliptical polarizing plate into a circular polarizing plate for the purpose of anti-reflection of an organic EL display device, the front retardation Re (550) of the phase difference layer 3 at a wavelength of 550nm is preferably 100 to 180nm, more preferably 110 to 170nm, further preferably 120 to 150nm, and may also be 125 to 145nm. The angle ψ formed by the absorption axis direction of the polarizer 10 and the slow axis direction of the phase difference layer 3 is preferably 40 to 50°, and may also be 43 to 47° or 44 to 46°.

[0065] When the phase difference layer 3 is a stack of multiple phase difference layers, and the slow axis directions in the plane of the multiple phase difference layers are not parallel, the angle ψ and the front retardation Re (550) calculated by the rotating analyzer method from the relationship between the angle θ of the analyzer obtained by the elliptically polarized light measurement through the elliptically polarized plate and the transmitted light intensity I (θ) are preferably within the above range. Hereinafter, the angle ψ and the front retardation obtained by the elliptically polarized light measurement are sometimes described as "apparent configuration angle" and "apparent front retardation".

[0066] The phase difference layer 3 includes at least one layer of oriented liquid crystal layer in which liquid crystal molecules are oriented along a plane. Figure 4 When the retardation layer 3 includes one retardation layer 31 as in the elliptically polarizing plate 101 shown in FIG. 1 , the retardation layer 31 is an aligned liquid crystal layer in which liquid crystal molecules are aligned along a plane.

[0067] The planar alignment liquid crystal layer is a positive A plate having a refractive index anisotropy of nx>ny≈nz, in which the alignment direction of the liquid crystal molecules is the slow axis direction, the refractive index nx in the slow axis direction (alignment direction of the liquid crystal), the refractive index ny in the fast axis direction in the plane, and the refractive index nz in the thickness direction. The planar alignment liquid crystal layer is formed, for example, by coating a liquid crystal composition containing a liquid crystal compound on a supporting substrate, aligning the liquid crystal compound in the planar direction, and then fixing the alignment state.

[0068] As liquid crystal compounds, rod-shaped liquid crystal compounds and disc-shaped liquid crystal compounds can be listed. From the aspect of being easy to orient along the surface by the orientation restriction force of the supporting substrate, as liquid crystal compounds, rod-shaped liquid crystal compounds are preferred. Rod-shaped liquid crystal compounds can be main chain liquid crystals or side chain liquid crystals. Rod-shaped liquid crystal compounds can be liquid crystal polymers or polymerizable liquid crystal compounds. As long as the liquid crystal compound (monomer) before polymerization shows liquid crystal properties, it can also not show liquid crystal properties after polymerization.

[0069] The liquid crystal compound is preferably a thermotropic liquid crystal that exhibits liquid crystal properties by heating. Thermotropic liquid crystals undergo phase transitions of a crystalline phase, a liquid crystal phase, and an isotropic phase by temperature changes. Examples of rod-shaped liquid crystal compounds that exhibit thermotropic properties include azomethines, azoxyls, cyanobiphenyls, cyanophenyl esters, benzoates, cyclohexanecarboxylic acid phenyl esters, cyanophenylcyclohexanes, cyano-substituted phenylpyrimidines, alkoxy-substituted phenylpyrimidines, phenyldioxanes, diphenylacetylenes, and alkenylcyclohexylbenzonitrile compounds.

[0070] Examples of polymerizable liquid crystal compounds include polymerizable liquid crystal compounds capable of fixing the alignment state of rod-shaped liquid crystal compounds using a polymer binder, polymerizable liquid crystal compounds having a polymerizable functional group capable of fixing the alignment state of liquid crystal compounds by polymerization, etc. Among them, photopolymerizable liquid crystal compounds having a photopolymerizable functional group are preferred.

[0071] The photopolymerizable liquid crystal compound (liquid crystal monomer) has a mesogen group and at least one photopolymerizable functional group in one molecule. The temperature at which the liquid crystal monomer exhibits liquid crystallinity (liquid crystal phase transition temperature) is preferably 40 to 200°C, more preferably 50 to 150°C, and further preferably 55 to 100°C.

[0072] As the mesogen unit group of the liquid crystal monomer, there can be listed cyclic structures such as biphenyl, phenyl benzoate, phenylcyclohexyl, azoxyphenyl, azomethine, azophenyl, phenylpyrimidinyl, diphenylethynyl, diphenylbenzoate, dicyclohexyl, cyclohexylphenyl, and terphenyl. The ends of these cyclic units may also have substituents such as cyano, alkyl, alkoxy, and halogen.

[0073] As the photopolymerizable functional group, (meth)acryloyl, epoxy, vinyl ether, etc. can be cited. Among them, (meth)acryloyl is preferred. The photopolymerizable liquid crystal monomer preferably has two or more photopolymerizable functional groups in one molecule. By using a liquid crystal monomer containing two or more photopolymerizable functional groups, since a cross-linked structure is introduced into the liquid crystal layer after photocuring, there is a tendency to improve the durability of the oriented liquid crystal layer.

[0074] As the photopolymerizable liquid crystal monomer, any suitable liquid crystal monomer can be used. For example, the compounds described in International Publication No. 00 / 37585, U.S. Patent No. 5211877, U.S. Patent No. 4388453, International Publication No. 93 / 22397, European Patent No. 0261712, German Patent No. 19504224, German Patent No. 4408171, British Patent No. 2280445, Japanese Unexamined Patent Application Publication No. 2017-206460, International Publication No. 2014 / 126113, International Publication No. 2016 / 114348, International Publication No. 2014 / 010325, Japanese Unexamined Patent Application Publication No. 2015-200877, Japanese Unexamined Patent Application Publication No. 2010-31223, International Publication No. 2011 / 050896, Japanese Unexamined Patent Application Publication No. 2011-207765, Japanese Unexamined Patent Application Publication No. 2010-31223, Japanese Unexamined Patent Application Publication No. 2010-270108, International Publication No. 2008 / 119427, Japanese Unexamined Patent Application Publication No. 2008-107767, Japanese Unexamined Patent Application Publication No. 2008-273925, International Publication No. 2016 / 125839, Japanese Unexamined Patent Application Publication No. 2008-273925, etc. can be cited. By selecting the liquid crystal monomer, the birefringence performance and the wavelength dispersion of the retardation can be adjusted, and a retardation layer 31 having a wavelength dispersion of Re(450) < Re(550) < Re(650) can also be formed from a single layer of a surface alignment liquid crystal layer.

[0075] A liquid crystal composition is prepared by mixing a liquid crystal monomer, various alignment control agents, a polymerization initiator, a leveling agent, etc. with a solvent, and an alignment liquid crystal layer is formed by coating it on a support substrate and aligning the liquid crystal compound. By using a flexible film as the support substrate, a series of processes from coating the liquid crystal composition on the support substrate to photocuring of the liquid crystal monomer and subsequent heat treatment can be carried out by roll-to-roll, so the productivity can be improved.

[0076] The support substrate may also have an alignment ability for aligning the liquid crystal compound in a specified direction. For example, by using a stretched film as the support substrate, the liquid crystal compound can be surface-aligned along its stretching direction. The stretching ratio of the stretched film only needs to be at a level where the alignment ability can be exerted, for example, about 1.1 times to 5 times. The stretched film may also be a biaxially stretched film. Even for a biaxially stretched film, as long as a stretched film with different stretching ratios in the longitudinal and transverse directions is used, the liquid crystal compound can be aligned along the direction with a larger stretching ratio. The stretched film may also be an inclined stretched film. By using an inclined stretched film as the support substrate, the liquid crystal compound can be aligned in a direction that is not parallel to either the length direction or the width direction of the support substrate.

[0077] The support substrate may also be provided with an alignment film on the surface where the oriented liquid crystal layer is formed. The alignment film may be selected appropriately according to the type of liquid crystal compound, the material of the support substrate, etc. As an alignment film for orienting the liquid crystal compound along a surface in a predetermined direction, an alignment film obtained by rubbing an alignment film of a polyimide system or a polyvinyl alcohol system may be suitably used. In addition, a photo-alignment film may also be used. It is also possible to perform a rubbing treatment on a resin film as a support substrate without providing an alignment film.

[0078] In the case where the liquid crystal compound is a thermotropic liquid crystal, the liquid crystal compound is oriented as a liquid crystal state by applying a liquid crystal composition on a supporting substrate and heating it. The liquid crystal phase is formed by heating the liquid crystal composition layer formed on the supporting substrate, so that the liquid crystal compound is oriented. Specifically, after the liquid crystal composition is applied to the supporting substrate, it is heated to above the N (nematic phase)-I (isotropic liquid phase) transition temperature of the liquid crystal composition to make the liquid crystal composition an isotropic liquid state. Thus, the nematic phase is exhibited by slow cooling as required. At this time, it is preferably temporarily maintained at a temperature that exhibits a liquid crystal phase, so that the liquid crystal phase domain grows and forms a single domain. Alternatively, after the liquid crystal composition is applied to the supporting substrate, the temperature is maintained for a certain period of time within the temperature range that exhibits a nematic phase to orient the liquid crystal compound in a specified direction.

[0079] The heating temperature for orienting the liquid crystal compound in a predetermined direction can be appropriately selected according to the type of liquid crystal composition, and is usually about 40 to 200°C. If the heating temperature is too low, there is a tendency that the transition to the liquid crystal phase becomes insufficient, and if the heating temperature is too high, the orientation defects sometimes increase. The heating time can be adjusted in a manner that the liquid crystal phase domain grows sufficiently, and is usually about 30 seconds to 30 minutes.

[0080] After the liquid crystal compound is aligned by heating, it is preferably cooled to a temperature below the glass transition temperature. The cooling method is not particularly limited, for example, it can be taken out of the heated atmosphere to room temperature. Forced cooling such as air cooling or water cooling can also be performed.

[0081] By irradiating the liquid crystal layer with light, the photopolymerizable liquid crystal compound (liquid crystal monomer) is photocured in a state with liquid crystal regularity. The irradiated light can be any light that can polymerize the photopolymerizable liquid crystal compound, and ultraviolet or visible light with a wavelength of 250 to 450 nm is usually used. When the liquid crystal composition is photocured, the liquid crystal compound can also be oriented in a specified direction by using polarized light in a specified direction. As described above, in the case where the liquid crystal compound is oriented by the orientation limiting force of the supporting substrate, the irradiated light can also be non-polarized light (natural light).

[0082] The polymer obtained by photocuring the liquid crystal monomer by light irradiation is non-liquid crystalline and does not undergo transitions between liquid crystal phase, glass phase, and crystalline phase due to temperature changes. Therefore, the liquid crystal layer photocured in a state where the liquid crystal monomer is oriented in a specified direction is less likely to have a change in molecular orientation due to temperature changes. When all the positive A plates are planar-aligned liquid crystal layers, there is a tendency to suppress changes in the front retardation and in-plane unevenness caused by heating, and to reduce the coloring of the reflected light at the shaped processing portion.

[0083] When the retardation layer 3 includes one planar-aligned liquid crystal layer 31, the planar-aligned liquid crystal layer 31 satisfies Re(450) < Re(550) < Re(650), and the angle ψ formed between the absorption axis direction of the polarizer 10 and the slow axis direction (liquid crystal orientation direction) of the planar-aligned liquid crystal layer 31 is 10 to 80°. When using the elliptical polarizer 101 as a circular polarizer, Re(550) of the planar-aligned liquid crystal layer 31 is preferably 100 to 180 nm, more preferably 110 to 170 nm, further preferably 120 to 150 nm, and may also be 125 to 145 nm. The angle ψ is preferably 40 to 50°, and may also be 43 to 47° or 44 to 46°.

[0084] As described above, the retardation layer 3 may also be a layer formed by laminating two or more retardation layers. As an example of an elliptical polarizer in which the retardation layer 3 is a laminate of two or more layers, there can be cited a configuration in which the retardation layer includes two (or more) positive A plates 32, 33 as shown in Figure 5 or a configuration in which the retardation layer 3 includes a positive A plate 31 as a planar-aligned liquid crystal layer and a positive C plate 36 as shown in Figure 6 In the elliptical polarizer 102 shown in

[0085] Figure 5 , the retardation layer 3 is formed by laminating two positive A plates 32, 33. As an example of the retardation layer 3 including two positive A plates, there can be cited a configuration in which the retardation layer 32 disposed on the side closer to the polarizer 1 is a half-wave plate and the retardation layer 33 disposed on the side farther from the polarizer 1 is a quarter-wave plate.

[0086] In this lamination configuration, it is preferably arranged such that the angle formed between the slow axis direction of the half-wave plate and the absorption axis direction of the polarizer is 75° ± 5°, and the angle formed between the slow axis direction of the quarter-wave plate and the absorption axis direction of the polarizer is 15° ± 5°. In this way, by laminating a plurality of retardation layers 32, 33 and the polarizer 10 at angles where their optical axes are neither parallel nor orthogonal, even when the retardation layers 32, 33 do not have inverse wavelength dispersion, it is possible to function as a circular polarizer in a wide wavelength range of visible light.

[0087] The principle of realizing broadband circularly polarized light by stacking a polarizer and a plurality of phase difference layers is described, for example, using the Poincare sphere in Japanese Patent Application Laid-Open No. 10-63816. The plurality of phase difference layers are not limited to the combination of a half-wave plate and a quarter-wave plate, but may be a stack of three or more phase difference layers. The configuration angle of each phase difference layer is not limited to the above, as long as the angle between the slow axis direction of each phase difference layer and the absorption axis direction of the polarizer is in the range of 10° to 80°.

[0088] When the phase difference layer 3 includes a plurality of positive A plates, as described above, the apparent configuration angle ψ is preferably 40 to 50°, and may be 43 to 47° or 44 to 46°. The apparent front retardation Re(550) of the phase difference layer 3 is preferably 100 to 180 nm, more preferably 110 to 170 nm, further preferably 120 to 150 nm, and may be 125 to 145 nm.

[0089] When the phase difference layer 3 includes two or more positive A plates, at least one positive A plate is a surface-aligned liquid crystal layer, and preferably all positive A plates are aligned liquid crystal layers. By making all of the plurality of positive A plates into surface-aligned liquid crystal layers, the thickness of the phase difference layer 3 can be reduced. In addition, as described above, by making all of the positive A plates into surface-aligned liquid crystal layers, there is a tendency to suppress the change in front retardation caused by heating, the in-plane unevenness, and the coloring of the reflected light at the irregularly processed portion.

[0090] As positive A plates other than the oriented liquid crystal layer, films of non-liquid crystal resin materials (polymers) can be cited. As polymers, polyester resins such as polycarbonate resins, polyethylene terephthalate, and polyethylene naphthalate, polyarylate resins, sulfone resins such as polysulfone and polyethersulfone, sulfide resins such as polyphenylene sulfide, polyimide resins, cyclic polyolefin resins (polynorbornene resins), polyamide resins, polyolefin resins such as polyethylene and polypropylene, and cellulose esters can be cited.

[0091] Figure 6 In the elliptically polarizing plate 103 shown in FIG. 1 , the retardation layer 3 is a stacked structure of a positive type A plate 31 and a positive type C plate 36. The positive type A plate 31 is a plane-aligned liquid crystal layer.

[0092] Figure 6 The elliptical polarizer 103 is equivalent to Figure 4The elliptical polarizer 101 is constructed by stacking a positive C plate having a refractive index anisotropy of nz>nx≈ny on the plane-oriented liquid crystal layer 31. By stacking a positive C plate on the positive A plate 31, the phase difference of the positive A plate in the tilt direction is eliminated by the positive C plate. Therefore, the stack of the positive A plate 31 and the positive C plate 36, i.e., the phase difference layer 3, has a refractive index anisotropy of nx>nz>ny, and the change in delay caused by the viewing angle is small. The circular polarizer having a phase difference layer formed by stacking a positive A plate and a positive C plate can reduce not only the reflected light on the front side of the display device, but also the reflected light in the tilt direction.

[0093] Examples of the positive C plate include a homeotropically aligned liquid crystal layer in which a liquid crystal compound is homeotropically aligned, and a film of a non-liquid crystal resin material (polymer) having negative intrinsic birefringence.

[0094] A polymer having negative intrinsic birefringence refers to a polymer whose refractive index in the orientation direction becomes relatively small when the polymer is oriented by stretching, etc. Examples of polymers having negative intrinsic birefringence include polymers having chemical bonds or functional groups with large polarization anisotropy such as aromatic or carbonyl groups introduced into the side chains of the polymers, and specifically, acrylic resins, styrene resins, maleimide resins, fumarate resins, etc.

[0095] The method for manufacturing the resin film is not particularly limited, and any of a solution method and a melt method can be used. When the resin film is formed by a solution method, the molecular chains of the polymer tend to be oriented in the in-plane direction. If the molecular chains of the polymer having negative intrinsic birefringence are oriented in the in-plane direction, the thickness direction refractive index nz of the coating becomes relatively smaller than the in-plane refractive index, and exhibits a positive C plate characteristic with a refractive index anisotropy of nz>nx≈ny (the thickness direction retardation Rth is a negative value). In addition, by biaxially stretching a film of a polymer having negative intrinsic birefringence in such a manner that the front retardation becomes approximately 0, a positive C plate with a front retardation of approximately 0 can be obtained. It should be noted that nx≈ny is not limited to the case where nx and ny are completely consistent, as long as the front retardation Re(550) at a wavelength of 550nm is less than 10nm. The front retardation Re(550) of the positive C plate is preferably less than 5nm, and can also be less than 3nm or less than 1nm.

[0096] From the viewpoint of reducing the thickness of the phase difference layer, the positive C plate 36 is preferably a vertically aligned liquid crystal layer. The vertically aligned liquid crystal layer is formed, for example, by coating a liquid crystal composition containing a liquid crystal compound on a supporting substrate and vertically aligning the liquid crystal compound and fixing the alignment state. For details of the vertically aligned liquid crystal layer, for example, reference can be made to Japanese Patent Application Publication No. 2008-216782.

[0097] The thickness direction retardation Rth of the positive C plate 36 represented by Rth=(nx-nz)×d is less than 0. It should be noted that nx and nz are as described above, and d is the thickness. The thickness direction retardation Rth of the positive C plate 36 is, for example, -30 to -200nm, preferably -50 to -150nm. The sum of the thickness direction retardation of the positive A plate 31 and the thickness direction retardation of the positive C plate 36 is preferably 30 to 110nm, more preferably 40 to 100nm, and further preferably 50 to 90nm.

[0098] exist Figure 6 In the figure, the phase difference layer 31 disposed on the side close to the polarizer 10 is a positive A plate of the plane-oriented liquid crystal layer, and the phase difference layer 36 disposed on the side away from the polarizer 10 is a positive C plate. However, the positive C plate may be disposed on the side close to the polarizer 10, and the positive A plate may be disposed on the side away from the polarizer 10. In addition, instead of the positive A plate 31 including one layer of the plane-oriented liquid crystal layer, a phase difference layer formed by stacking a plurality of positive A plates 32 and 33 may be used.

[0099] [Elliptical polarizer]

[0100] An elliptically polarizing plate is formed by laminating the phase difference layer 3 on the transparent protective film 11 on one surface of the polarizing plate 1. The arrangement angle between the polarizer 10 and the phase difference layer 3 of the polarizing plate 1 is as described above.

[0101] The polarizing plate 1 and the phase difference layer 3 are preferably bonded together via a suitable adhesive or bonding agent. Figure 5 and Figure 6 As shown in , when the phase difference layer 3 is a laminate of multiple phase difference layers, the multiple phase difference layers can be pre-laminated and then laminated to the polarizer, or multiple phase difference layers can be laminated sequentially on the polarizer. For laminating multiple phase difference layers, a suitable adhesive or binder is used. The phase difference layer 3 may also include a film or an oriented film used as a supporting substrate when the oriented liquid crystal layer is formed.

[0102] In addition to the polarizing plate and the phase difference layer, the elliptical polarizing plate may also have various additional layers, such as an antireflection layer, an adhesive for bonding the elliptical polarizing plate to an image display unit, and a surface protection film for protecting the surface of the elliptical polarizing plate.

[0103] As described above, the elliptically polarizing plate of the present invention is processed into a special shape. From the viewpoint of productivity, it is preferred that the special shape processing be performed after laminating the layers constituting the elliptically polarizing plate.

[0104] [Image display device]

[0105] Figure 7It is a cross-sectional view showing an example of a stacked structure of an image display device, in which the surface of the image display unit 50 is bonded to the surface of the phase difference layer 3 side of the elliptical polarizing plate 105 via an adhesive layer not shown. The oriented liquid crystal film may also have more than two oriented liquid crystal layers. As the image display unit 50, a liquid crystal unit, an organic EL unit, etc. may be listed. The elliptical polarizing plate of the present invention may be used as a circular polarizing plate for shielding the reflected light of the external light of the vehicle-mounted organic EL display device.

[0106] Image display devices for vehicles are required to have small changes in display characteristics even when exposed to high temperature environments for a long time. When a circular polarizer that has been processed by a special shape is applied to an organic EL display device, the coloring of reflected light is easily visible around the special shape processing part such as a notch in a high temperature environment. The cause of this was studied and it was found that the large unevenness of the change in the front retardation during the high temperature durability test around the special shape processing part is one of the factors that easily causes the coloring of reflected light.

[0107] Figure 8 This is an enlarged view of the periphery of the shaped processed portion of the circular polarizer that has been processed by the shaped process. The oblique lines in the figure indicate the slow axis direction of the phase difference layer. For the conventional shaped processed circular polarizer, after the heating durability test, the front retardation of region A in the figure is more than 10nm greater than the front retardation of region B. The reflected light of region A with relatively large front retardation is colored and can be seen as blue, and the reflected light of region B with relatively small front retardation is colored and can be seen as red. In the case where the shaped processed portion is a notch, since region A and region B are close, it is easy to identify the difference in color.

[0108] If the elliptically polarizing plate is exposed to a high temperature environment, stress is generated at the lamination interface between the layers due to the difference in the heating dimensional change rate of the polarizer, transparent protective film and phase difference layer, which becomes the cause of the change in the delay of the phase difference layer. Stretched films tend to shrink greatly when heated in the stretching direction. For elliptically polarizing plates configured at an angle that is neither parallel nor orthogonal to the absorption axis direction of the polarizer and the slow axis direction of the phase difference layer, the heating shrinkage of the polarizer (polarizer) and the heating shrinkage of the phase difference layer are different, so the change in the delay of the phase difference layer due to stress is likely to become larger.

[0109] For a single elliptically polarized plate, it is believed that stress is easily relaxed near the outer edge, but in region A where the slow axis direction of the phase difference layer is roughly parallel to the processing direction of the profiled processed portion (the contact direction of the outer edge) and in region B where the slow axis direction of the phase difference layer is roughly orthogonal to the processing direction of the profiled processed portion, the difference in the delay change caused by heating becomes larger due to different stress relaxation behaviors.

[0110] In the elliptically polarizing plate of the present invention, since the thickness of the polarizer 10 is as large as 15 μm or more, and transparent protective films 11 and 12 are laminated on both sides of the polarizer 10, the dimensional change of the polarizing plate 1 can be suppressed. Furthermore, since the positive A plate of the phase difference layer 3 is a plane-oriented liquid crystal layer, the dimensional change due to heating is smaller than that of a stretched film, and thus the change in the front retardation of the phase difference layer 3 caused by heating can be suppressed. In addition, it is believed that the oriented liquid crystal layer after solidification in the state where the liquid crystal compound is oriented does not undergo phase change due to temperature change, and the fixed orientation state is also a factor that can suppress the retardation change caused by heating.

[0111] The elliptical polarizer of the present invention includes a plane-oriented liquid crystal layer through the phase difference layer 3, and even in a region with a small area and a large change in processing angle such as an R-shaped or V-shaped notch, the unevenness of the front retardation of the phase difference layer after the heating durability test is small. Therefore, the difference in color around the special-shaped processing part is not easy to be identified, and the display characteristics are excellent. Such a special-shaped elliptical polarizer can be suitably used for a vehicle-mounted image display device that is required to have a small change in characteristics under a high temperature environment.

[0112] Example

[0113] Hereinafter, the present invention will be described in more detail with reference to Examples and Comparative Examples, but the present invention is not limited to the following examples.

[0114] [Comparative Example 1]

[0115] <Production of polarizing plate>

[0116] Transparent protective films were bonded to both sides of a stretched polyvinyl alcohol polarizer with a thickness of 18 μm using an ultraviolet curing adhesive. As a transparent protective film on one side, a triacetyl cellulose film (total thickness 49 μm) having a hard coating layer with a thickness of 3 μm was used on one side, and the side without the hard coating layer was bonded to the polarizer. As a transparent protective film on the other side, a stretched film (thickness 30 μm) of a modified acrylic resin with a lactone ring structure introduced was used.

[0117] <Production of Phase Difference Layer>

[0118] (Production of polycarbonate film)

[0119] According to the method described in Example 1 of Japanese Patent No. 5204200, a polycarbonate resin containing a constituent unit derived from isosorbide (37.1 mol%), a constituent unit derived from 9,9-bis[4-(2-hydroxyethoxy)phenyl]fluorene (47.4 mol%), and a constituent unit derived from 1,4-cyclohexanedimethanol (15.5 mol%) was prepared, formed into a film, and stretched. The stretched polycarbonate film was a positive A plate having a refractive index anisotropy of nx>ny=nz, with a thickness of 37 μm, Re(450)=123 nm, Re(550)=144 nm, and Re(650)=152 nm.

[0120] (Fabrication of Vertically Aligned Liquid Crystal Layer)

[0121] A liquid crystal composition is prepared by dissolving 20 parts by weight of a side chain liquid crystal polymer having a weight average molecular weight of 5000 of the following chemical formula (n=0.35, expressed as a block polymer for convenience), 80 parts by weight of a polymerizable liquid crystal compound showing a nematic liquid crystal phase ("Paliocolor LC242" manufactured by BASF), and 5 parts by weight of a photopolymerization initiator ("Omnirad907" manufactured by IGM Resins) in 400 parts by weight of cyclopentanone.

[0122] [Chemical formula 1]

[0123]

[0124] The liquid crystal composition was applied on the surface of a biaxially stretched norbornene film (ZEONOR FILM manufactured by ZEON Japan, thickness: 52 μm, front retardation: 50 nm) by a bar coater so that the thickness after drying would be 1 μm, and the liquid crystal was aligned by heating at 80°C for 2 minutes. After cooling to room temperature, the film was irradiated with 700 mJ / cm 2 The liquid crystal monomer was photocured by ultraviolet light to obtain a laminate A having a vertically aligned liquid crystal layer (3 μm thick) formed on a film substrate. The vertically aligned liquid crystal layer was a positive C plate with a refractive index anisotropy of nz>nx=ny, and the thickness direction retardation Rth(550) at a wavelength of 550 nm measured by transferring the vertically aligned liquid crystal layer to a glass plate was 100 nm.

[0125] (Preparation of Adhesive)

[0126] 50 parts by weight of unsaturated fatty acid hydroxyalkyl ester-modified ε-caprolactone ("PLACCEL FA1DDM" manufactured by Daicel), 25 parts by weight of acryloylmorpholine ("ACMO" manufactured by Kojin), 10 parts by weight of polypropylene glycol (n=3) diacrylate ("Aronix M-220" manufactured by Toagosei), 15 parts by weight of an epoxy-containing acrylic oligomer having a weight average molecular weight of 2,900 ("ARFON UG-4100" manufactured by Toagosei), and 2 parts by weight of "Omnirad 907" and 2 parts by weight of "KAYACURE DETX-S" (manufactured by Nippon Kayaku) as photopolymerization initiators were mixed to prepare an ultraviolet-curable adhesive composition A.

[0127] (Polycarbonate film and vertical alignment liquid crystal layer bonding)

[0128] The polycarbonate film and the surface of the vertically aligned liquid crystal layer of the laminate A were subjected to corona treatment, and then the adhesive composition A was applied and laminated using a roll laminator. The laminate was then irradiated with 700 mJ / cm2 of UV curing equipment (V-valve) manufactured by Fusion UV Systems. 2 The adhesive is cured by ultraviolet rays to obtain a laminated phase difference layer in which the polycarbonate film and the vertically aligned liquid crystal layer are bonded together via the adhesive layer.

[0129] <Production of Circular Polarizing Plate>

[0130] The surface of the acrylic film side of the polarizer is bonded to the surface of the polycarbonate film side of the above-mentioned laminated phase difference layer via an acrylic adhesive sheet with a thickness of 20 μm. At this time, the angle formed by the absorption axis direction of the polarizer and the stretching direction (slow axis direction) of the polycarbonate film is set to 45°. Afterwards, the film substrate is peeled off and removed from the surface of the vertically aligned liquid crystal layer, and an acrylic adhesive sheet with a thickness of 23 μm is bonded to the surface of the exposed vertically aligned liquid crystal layer. By operating in this way, a circular polarizer with an adhesive is obtained in which an adhesive sheet is laminated on a laminate (circular polarizer) in which a stretched polycarbonate film is bonded to the polarizer via an adhesive layer and a vertically aligned liquid crystal layer is bonded thereon via an adhesive layer.

[0131] <Processing of Circular Polarizing Plate>

[0132] The circular polarizing plate with adhesive was punched out into a 300 mm × 100 mm rectangle with the absorption axis of the polarizer set as the long side using a Thomson knife. Then, a bathtub-shaped cut was made on one long side and an R-shaped (semicircular) cut was made on the other long side using an end mill. Fig. 9 The curvature radius of the curved portion of the cutout is set to 10 mm.

[0133] [Comparative Example 2]

[0134] <Production of Phase Difference Layer>

[0135] (Fabrication of 1 / 4 Wavelength Plate)

[0136] A film was made using polycarbonate resin ("DURABIO" manufactured by Mitsubishi Chemical) and subjected to free-end uniaxial stretching. The stretched film (1 / 4 wavelength plate) was a positive A plate with a refractive index anisotropy of nx>ny=nz, a thickness of 20 μm, Re(450)=143 nm, Re(550)=140 nm, and Re(650)=137 nm.

[0137] (Fabrication of 1 / 2 Wavelength Plate)

[0138] The thickness and stretching ratio of the above film were changed to obtain a stretched film (half-wavelength plate) having a thickness of 40 μm, Re(450)=277 nm, Re(550)=270 nm, and Re(650)=265 nm.

[0139] (Production of Adhesive Sheet)

[0140] In a reaction vessel, 92 parts by weight of butyl acrylate, 5 parts by weight of N-acryloylmorpholine, 2.9 parts by weight of acrylic acid, and 0.1 parts by weight of 2-hydroxyethyl acrylate as monomers, and 0.1 parts by weight of azobisisobutyronitrile as a polymerization initiator were added together with ethyl acetate, and reacted at 55°C for 8 hours under a nitrogen gas stream. Thereafter, ethyl acetate was added to the reaction solution to obtain a solution of an acrylic polymer having a weight average molecular weight of 1.78 million. To this solution, 0.15 parts by weight of dibenzoyl peroxide ("NYPER BMT" manufactured by NOF Corporation) as a crosslinking agent and 0.6 parts by weight of trimethylolpropane / tolylene diisocyanate adduct ("CORONATE L" manufactured by Tosoh Corporation) were added to 100 parts by weight of the polymer to obtain an adhesive composition. The PSA composition was applied to a release-treated surface of a 38 μm thick polyethylene terephthalate film (MRF38 manufactured by Mitsubishi Chemical), dried and cross-linked at 150° C. to prepare a 5 μm thick PSA sheet A.

[0141] <Production of Circular Polarizing Plate>

[0142] The above-mentioned 1 / 2 wavelength plate is bonded to the surface of the acrylic film side of the polarizer. At this time, the angle formed by the absorption axis direction of the polarizer and the stretching direction (slow axis direction) of the 1 / 2 wavelength plate is set to 75°. Afterwards, a 1 / 4 wavelength plate is bonded to the surface of the 1 / 2 wavelength plate via adhesive sheet A. At this time, the angle formed by the absorption axis direction of the polarizer and the stretching direction (slow axis direction) of the 1 / 4 wavelength plate is set to 15°. Afterwards, an acrylic adhesive sheet with a thickness of 23 μm is bonded to the 1 / 4 wavelength plate. By operating in this way, a circular polarizer with an adhesive is obtained, in which an adhesive sheet is laminated on a laminate (circular polarizer) in which a 1 / 2 wavelength plate containing a stretch film is bonded to the polarizer via an adhesive layer, and a 1 / 4 wavelength plate containing a stretch film is bonded thereon via an adhesive layer. The circular polarizer with an adhesive is processed into a special shape in the same way as in Comparative Example 1.

[0143] [Example 1]

[0144] <Production of Phase Difference Plate>

[0145] (Production of Planar Alignment Liquid Crystal Layer)

[0146] 55 parts by weight of the compound represented by formula (I), 25 parts by weight of the compound represented by formula (II), and 20 parts by weight of the compound represented by formula (III) are added to 400 parts by weight of cyclopentanone, heated to 60°C and stirred to dissolve, and then cooled to room temperature to prepare a solution with a solid content concentration of 20% by weight.

[0147] [Chemical formula 2]

[0148]

[0149] To this solution, 0.2 parts by weight of a leveling agent ("MEGAFACE F-554" manufactured by DIC), 3 parts by weight of a photopolymerization initiator (Omnirad 907), and 0.1 parts by weight of p-methoxyphenol were added to prepare a liquid crystal composition solution.

[0150] As a film substrate, a film having a rubbing-treated alignment film on a triacetyl cellulose film was used. The above-mentioned liquid crystal composition was applied to the alignment film of the film substrate by spin coating, and heated at 100°C for 2 minutes to align the liquid crystal. After cooling to room temperature, the film was irradiated in a nitrogen atmosphere with a cumulative light intensity of 900 mJ / cm 2 The film was photocured by ultraviolet light to obtain a laminate B having a plane-oriented liquid crystal layer (3 μm thick) formed on a film substrate. The plane-oriented liquid crystal layer was a positive A plate with a refractive index anisotropy of nx>ny=nz. The front retardation measured by transferring the plane-oriented liquid crystal layer to a glass plate was Re(450)=118nm, Re(550)=145nm, and Re(650)=152nm.

[0151] (Attachment of the planar alignment liquid crystal layer and the vertical alignment liquid crystal layer)

[0152] The surfaces of the laminate A and the laminate B on the oriented liquid crystal layer side were subjected to corona treatment, and then the adhesive composition A was applied thereto, and the laminate was laminated using a roll laminator. The laminate was then irradiated with a UV curing device (V valve) manufactured by Fusion UV Systems at 700 mJ / cm 2 The adhesive is cured by ultraviolet light to obtain a laminated phase difference layer in which the vertically aligned liquid crystal layer and the planarly aligned liquid crystal layer are bonded together via the adhesive layer.

[0153] <Manufacturing and processing of circular polarizing plates>

[0154] The film substrate is peeled off and removed from the surface of the plane-oriented liquid crystal layer of the above-mentioned stacked phase difference layer, and the surface of the acrylic film side of the polarizer is bonded to the surface of the exposed plane-oriented liquid crystal layer via an acrylic adhesive sheet with a thickness of 20 μm. At this time, the angle formed by the absorption axis direction of the polarizer and the orientation direction (slow axis direction) of the plane-oriented liquid crystal layer is set to 45°. After that, the film substrate is peeled off and removed from the surface of the vertically oriented liquid crystal layer, and an acrylic adhesive sheet with a thickness of 23 μm is bonded to the surface of the exposed vertically oriented liquid crystal layer. By operating in this way, a circular polarizer with an adhesive is obtained, in which an adhesive sheet is laminated on a laminate (circular polarizer) in which a plane-oriented liquid crystal layer is bonded to the polarizer via an adhesive layer and a vertically oriented liquid crystal layer is bonded thereon via an adhesive layer. The circular polarizer with an adhesive is processed into a special shape in the same way as in Comparative Example 1.

[0155] [Example 2]

[0156] <Production of Phase Difference Layer>

[0157] (Production of Planar Alignment Liquid Crystal Layer (1 / 4 Wavelength Plate))

[0158] A photopolymerizable liquid crystal compound ("Paliocolor LC242" manufactured by BASF) showing a nematic liquid crystal phase was dissolved in cyclopentanone to prepare a solution having a solid content concentration of 30% by weight. A leveling agent ("BYK-360" manufactured by BYK-Chemie) and a photopolymerization initiator (Omnirad907) were added to the solution to prepare a liquid crystal composition solution. The amount of the leveling agent and the polymerization initiator added was set to 0.01 parts by weight and 3 parts by weight, respectively, relative to 100 parts by weight of the photopolymerizable liquid crystal compound.

[0159] As a film substrate, a biaxially stretched norbornene film (ZEONOR FILM manufactured by ZEON Japan, thickness: 33 μm) was used. The above-mentioned liquid crystal composition was applied to the surface of the film substrate using a bar coater so that the thickness after drying was 1 μm, and the liquid crystal was oriented by heating at 100°C for 3 minutes. After cooling to room temperature, the film was irradiated in a nitrogen atmosphere with a cumulative light intensity of 400 mJ / cm 2 The film was photocured by ultraviolet light to obtain a laminate C having a planar-oriented liquid crystal layer (thickness 1 μm) formed on a film substrate. The planar-oriented liquid crystal layer was a positive A plate with a refractive index anisotropy of nx>ny=nz. The front retardation measured by transferring the planar-oriented liquid crystal layer to a glass plate was Re(450)=156nm, Re(550)=144nm, and Re(650)=138nm.

[0160] (Production of Planar Alignment Liquid Crystal Layer (1 / 2 Wavelength Plate))

[0161] The same operation as above was performed except for changing the coating thickness of the liquid crystal composition to obtain a stack D having a surface-oriented liquid crystal layer with a thickness of 2 μm, Re(450)=300 nm, Re(550)=280 nm, and Re(650)=268 nm formed on a film substrate.

[0162] <Production of Circular Polarizing Plate>

[0163] The surface on the side of the oriented liquid crystal layer of the above-mentioned stack D is bonded to the surface on the side of the acrylic film of the polarizer via an acrylic adhesive sheet with a thickness of 20 μm. At this time, the angle formed by the absorption axis direction of the polarizer and the orientation direction (slow axis direction) of the plane-oriented liquid crystal layer (1 / 2 wavelength plate) is set to 75°. Thereafter, the film substrate is peeled off and removed from the surface of the plane-oriented liquid crystal layer, and the surface on the side of the plane-oriented liquid crystal layer of the stack C is bonded via adhesive sheet A to the surface of the exposed plane-oriented liquid crystal layer. At this time, the angle formed by the absorption axis direction of the polarizer and the orientation direction (slow axis direction) of the plane-oriented liquid crystal layer (1 / 4 wavelength plate) is set to 15°. Thereafter, the film substrate is peeled off and removed from the surface of the plane-oriented liquid crystal layer, and an acrylic adhesive sheet with a thickness of 23 μm is bonded. By operating in this way, a circular polarizer with adhesive is obtained, in which an adhesive sheet is laminated on a laminate (circular polarizer) in which a planar-oriented liquid crystal layer (1 / 2 wavelength plate) is laminated on a polarizer via an adhesive layer and a planar-oriented liquid crystal layer (1 / 4 wavelength plate) is laminated on the laminate (circular polarizer) via an adhesive layer. The circular polarizer with adhesive is processed into a special shape in the same manner as in Comparative Example 1.

[0164] [evaluate]

[0165] <Phase difference change>

[0166] The adhesive sheet provided on the surface of the phase difference layer of the polarizing plate with adhesive of the Example and the Comparative Example was bonded to a glass plate to prepare a sample for evaluation. Fig. 9 The front retardation (initial value) at a wavelength of 550 nm was measured at the seven locations (1) to (7) shown in the figure using a phase difference meter (manufactured by Oji Scientific Instruments, "KOBRA 21-ADH") in the ellipsometric mode. The evaluation sample was then placed in an air circulation constant temperature oven at 95°C, and the front retardation was measured after 240 hours.

[0167] Table 1 shows the difference ΔRe between the maximum value and the minimum value of the surface retardation at seven locations of the sample after the heat durability test at 95° C. for 240 hours and the standard deviation σ.

[0168] Table 1

[0169]

[0170] <Changes in reflected light hue>

[0171] For the circular polarizing plates of Comparative Example 1 and Example 2, the evaluation sample obtained by laminating the adhesive sheet attached to the surface of the phase difference layer to the glass plate was placed on an aluminum vapor-deposited film (manufactured by Toray) in such a way that the surface on the glass plate side was on the lower side. The hue of the reflected light when white light was incident from the polarizing plate side was measured using a spectrophotometer ("CM-26" manufactured by Konica Minolta). Fig. 9 The 7 locations of (1) to (7) shown in FIG. 1 were implemented. After the evaluation sample was subjected to the heat durability test at 95° C. for 240 hours, the reflected light hue at the 7 locations was measured again.

[0172] will be in a * b * The hue plane plots the reflected light hue (▲) before the heating test and the reflected light hue (○) after the heating durability test. Fig. 10A and Fig. 10B In. Fig. 10A and Fig. 10B In the figure, the horizontal axis is a * , the vertical axis is b * .

[0173] Compared with Comparison Examples 1 and 2 using a stretched film as the positive A plate, Examples 1 and 2 using a plane-oriented liquid crystal layer as the positive A plate show that the in-plane unevenness of the front retardation in the circular polarizer after the heating durability test becomes smaller, and as a result, the unevenness of the reflected light hue is less, and the plate has uniform characteristics.

Claims

1. An elliptical polarizer, which is a single-piece elliptical polarizer, comprising: a polarizer having a polarizer, a first transparent protective film attached to the first main surface of the polarizer, and a second transparent protective film attached to the second main surface of the polarizer; and a retardation layer attached to the first transparent protective film of the polarizer, having a non-rectangular shaped abnormal shape in a top view, the angle formed by the absorption axis direction of the polarizer and the slow axis direction of the retardation layer is 10 to 80°, the thickness of the polarizer is 15 μm or more, the front retardation Re(450) at a wavelength of 450 nm, the front retardation Re(550) at a wavelength of 550 nm, and the front retardation Re(650) at a wavelength of 650 nm of the retardation layer satisfy Re(450) < Re(550) < Re(650), and include at least one alignment liquid crystal layer in which liquid crystal molecules are aligned in the plane.

2. The elliptically polarizing plate according to claim 1, wherein: The retardation layer includes two or more alignment liquid crystal layers, and at least one of them is an alignment liquid crystal layer in which liquid crystal molecules are aligned in the plane.

3. The elliptically polarizing plate according to claim 1, wherein: The retardation layer includes an alignment liquid crystal layer in which liquid crystal molecules are aligned in the plane and an alignment liquid crystal layer in which liquid crystal molecules are vertically aligned.

4. The elliptically polarizing plate according to claim 1, wherein: The retardation layer includes two or more alignment liquid crystal layers in which liquid crystal molecules are aligned in the plane, and the angle formed by the slow axis directions of the plurality of alignment liquid crystal layers is 10 to 80°.

5. A vehicle-mounted image display device, which is provided with the elliptical polarizer according to any one of claims 1 to 4 on the visible side surface of an image display unit.

6. The vehicle-mounted image display device according to claim 5, wherein: The image display unit is an organic EL unit.

Citation Information

Patent Citations

  • Liq. crystalline (LC) material

    DE19504224A1

  • Novel polymerizable liquid crystalline compounds

    DE4408171A1

  • Liquid crystalline copolymer

    GB2280445A

  • Fluorescence eye catcher sighhboard by stimulation of ultraaviolet ray s

    JP1977004200A

  • Picture reading device

    JP1998063816A